Generation Why Not? - Klein, Ruth (HighBridge, 2020)
Join the ranks of Generation Why Not?®-a generation driven by attitude rather than age-to reach your dreams and goals in business and life. Generation Why Not?® lays out seven principles that many highly successful people hold as their core beliefs about business and life. They know it's not about your age, your gender, or your background-it's about your attitude. Through personal interviews with and observations of a diverse community of individuals ranging from multi-millionaire CEOs, to octogenarians starting new careers, to second and third do-overs, to young adults reinventing the world, author Ruth Klein offers insights and practical applications you can start using to begin to see your life and work through a new lens-one of clarity and purpose. Once you've embraced the tools of Generation Why Not?®, you'll no longer adhere to "I have to see it to believe it." First, you'll believe it-and then everyone will see it.